Employee motivation in medium-sized manufacturing enterprises : two case studies from northern Sweden - Edlund, Malin; Nilsson, Hanna (2007)
Motivation continues to be a well-researched topic both by academics and commercial firms. The aim of work motivation is to have well motivated employees as well as having managers with the possibility to motivate others. The focus is on the factors managers use to motivate employees and the differences regarding gender and age. The purpose with the study is to provide a better understanding of the employee motivation issues in small and medium-sized Swedish enterprises. In order to reach this purpose, three research questions were stated: how Swedish managers motivate their employees in SMEs, and on the relationship between gender, age and motivation. A qualitative, case study methodology was used to interview two companies in northern Sweden: Polarbröd and Älvsbyhus. The findings show that motivation is very individual and managers have a hard task motivating their employees. Today employees are more motivated by intrinsic factors rather than extrinsic which dominated in the past, but none of the two can be overlooked by managers when motivating their employees. The most revealing finding concerning gender and age is that managers do not motivate their employees differently concerning these two variables. Validerat; 20101217 (root)